Pulmonary capillary recruitment in exercise and pulmonary hypertension. Issue 3 (15th March 2018) - Langleben, David; Orfanos, Stylianos E.
We read with interest the excellent European Respiratory Society statement on exercise pulmonary hypertension (PH) by Kovacs et al. [1] in the European Respiratory Journal . Fundamentally, exercise PH, especially with precapillary causes such as pulmonary arterial hypertension (PAH), is an inability of the lung circulation to accommodate increased blood flow during exercise. Although the authors mention "distention" of the vasculature, implying stretching of already perfused vessels, the increased pulmonary blood flow is primarily accommodated in the normal lung by recruitment of unused capillaries, allowing the pulmonary artery pressure to change minimally during exercise [2, 3]. Further evidence of this recruitment is found in true vasoresponders during an acute vasodilator challenge for evaluation of idiopathic PAH [4]. By contrast, because it is caused by precapillary vascular obstruction and not vasoconstriction, vasodilator-nonresponsive PAH accommodates any increased cardiac output via distention and not via recruitment [5]. We have also observed pulmonary capillary recruitment in normal humans during exercise (unpublished data). Recruitment is a normal physiological process, and it is impaired in many types of PH. As we move forward in our understanding of exercise PH and its physiology, precise definitions and semantics will be critical. Pulmonary capillary recruitment is important in the pulmonary haemodynamic response to exercise http://ow.ly/tKJm30icJkp